Perceptions and stress factors among physicians in pre-graduate and post-graduate training in Morocco: COVID-19 pandemic context - Adil Mansouri; Majda Sebbani; Latifa Adarmouch; Ouassim Mansoury; Mohamed Amine (Greater Baltimore Medical Center, 2021)
Context: On 30 January, 2020, WHO stated that the global COVID-19 epidemic is a public health emergency. Facing this critical situation, health-care workers were at risk of developing psychological distress and other mental health problems. Aims: This study seeks to explore the feelings, attitudes and perceptions of the COVID-19 pandemic among physicians in pre-graduate and post-graduate training from Marrakesh University Hospital Centre. Methods and Material:We conducted a cross-sectional study with internal and resident-physicians in May 2020. Data collection was based on a self-administered electronic questionnaire. The sociodemographic informations, pandemic impact on the occupational and social fields and stress factors were evaluated. Statistical significance was set at p < 0.05. Results: The number of participants was 74. The sex ratio was 1.4 with an average age of 26.1 ± 3.6 years. Two-thirds were directly involved in the management of patients with SARS-CoV2. The majority reported that their work puts them at high-risk of exposure to SARS-CoV2 and 66% felt stressed at work, female physicians were more stressed than men (p = 0.028). Not knowing when the pandemic will be under control and the risk of developing an infection with SARS-CoV2 were the main sources of stress. About motivators for similar situations, respondents emphasized family support (91.9%) and recognition by management and supervisors for the additional efforts they provide (83.8%). Conclusions: The protection of health-care workers is an important component of public health measures to combat this pandemic. Special interventions to promote health-care workers mental well-being must be implemented immediately.